Measuring the efficiency of the Indonesian Air Police using Data Envelopment Analysis with BCC Model - Pradanarka, Andyas Mukti; Nugraha, Isna; Rakhmanhuda, Iffad (LPPM Universitas Dian Nuswantoro, 2025)
As part of the Indonesian National Police, one of the tasks of the Air Police is to support the Ministry of Environment and Forestry in preventing deforestation. With the available resources, the Air Police must be able to carry out their duties efficiently. This study measures the efficiency of the support performance of ten Air Police under the Control of the Regional Police covering ten provinces to prevent deforestation. Each operations control (OC) represents a Decision-Making Unit (DMU). Using Data Envelopment Analysis (DEA) with the Banker, Charnes, Cooper (BCC) model, the results showed that two OCs (Bali and North Sulawesi) were identified as efficient, while eight OCs were inefficient. Keywords - deforestation, efficiency, DEA, BCC, VRS